2019
DOI: 10.1007/s11712-019-09669-0
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors of Metaphors: Reflections on the Use of Conceptual Metaphor Theory in Premodern Chinese Texts

Abstract: In this essay, I challenge the use of Conceptual Metaphor Theory (CMT) in the premodern Chinese setting. The dominant, implicit assumption in the literature is that conclusions reached by CMT on the ways in which cognition operates can be applied in toto and without qualification onto the makers of classical Chinese texts. I want to challenge this assumption and argue that textual evidence from premodern Chinese points to a different cognitive process. Differences in the use and conceptualization of image-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This phenomenon was also found in Chinese physiognomy, which showed that it is easier to view a person with a straight nose as virtuous and a person with a curved nose as immoral. The reason people are generally unaware of the prevalence of metaphors in language and their lives is because metaphors are by their very nature hidden since, unlike similes, they do not employ special linguistic markers [ 45 ]. If the existence of curvilinear metaphors for moral concepts is demonstrated in this study, it can help people to understand more about moral metaphors, so that we can intentionally control these metaphorical elements and sound the alarm in order to reduce stereotypes and other biased behaviors in real life.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was also found in Chinese physiognomy, which showed that it is easier to view a person with a straight nose as virtuous and a person with a curved nose as immoral. The reason people are generally unaware of the prevalence of metaphors in language and their lives is because metaphors are by their very nature hidden since, unlike similes, they do not employ special linguistic markers [ 45 ]. If the existence of curvilinear metaphors for moral concepts is demonstrated in this study, it can help people to understand more about moral metaphors, so that we can intentionally control these metaphorical elements and sound the alarm in order to reduce stereotypes and other biased behaviors in real life.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous scholars have conducted a significant amount of research into CM from various perspectives, such as psycholinguistic metaphor research (Murphy, 1996;Gibbs, 2013;Qiu et al, 2022); deliberate metaphors and embodied simulation research (Gibbs, 2006;Cuccio and Steen, 2019;Cuccio et al, 2022); conceptual conflicts in metaphors and translation (Prandi, 2017;Rizzato, 2021Rizzato, , 2022; corpus-based metaphor research (Sinclair, 1991;Charteris-Black, 2000Semino, 2002;Deignan and Potter, 2004;Allen, 2006;Fabiszak, 2007;Tissari, 2010;Shutova et al, 2013;Burgers and Ahrens, 2018;Zhao and Zhou, 2019;Zhao et al, , 2020Silvestre-López, 2020;Bosman and Taljard, 2021;Kazemian and Hatamzadeh, 2022), critical metaphors in discourse analysis (Charteris-Black, 2004;Ferrari, 2007;Musolff, 2012) and metaphors in classroom teaching (Thomas and McRobbie, 2001;Andreou and Galantomos, 2008). There is also increasing research on various reviews of CM research (e.g., Allahmoradi, 2018;Holyoak and Stamenkovic, 2018;Bundgaard, 2019;Gandolfo, 2019;Tohidian and Rahimian, 2019;Kövecses, 2020;Bearman et al, 2021;Jensen et al, 2021;Abdul et al, 2022).…”
Section: Conceptual Metaphor Researchmentioning
confidence: 99%
“…However, keeping up with everything published instantaneously becomes more problematic. In terms of CM research, there are increasing studies on linked subjects, and various reviews have been conducted (e.g., Allahmoradi, 2018;Holyoak and Stamenkovic, 2018;Bundgaard, 2019;Gandolfo, 2019;Tohidian and Rahimian, 2019;Kövecses, 2020;Bearman et al, 2021;Jensen et al, 2021;Abdul et al, 2022). However, these studies mainly focused on qualitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Its legacy, from the early shi of the Book of Songs to the masterpieces of the Tang dynasty, encapsulates a wealth of philosophical traditions within its layered metaphors and aesthetic complexities [1]. The complex interplay of language, historical allusions, and metaphorical richness in these works transcends conventional linguistic analysis, requiring an intimate understanding of the cultural and philosophical contexts that shape them [3,4].…”
Section: Introductionmentioning
confidence: 99%